Kazakhstan Economic Update, Summer 2020 : Navigating the Crisis - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 pandemic has turned the world economy upside down. As recently as January 2020, analysts and various institutions projected that, this year, the global economy would haverecovered from the lowest growth since post-global financial crisis. But instead, developed and developing countries are fighting against the fallout from the pandemic. The global economy entereda serious recession in February, and global commodity prices tumbled. The earlier failure of OPEC and its allies to agree on a production cut amplified the impact of weakening global demand onoil exporters like Kazakhstan. Weaker activity, travel restrictions, and reduced mobility are projected to reduce global demand for oil by 9 percent in 2020. The pandemic, the economic slump,and the stress on the corporate and financial sectors are mutually dependent, and the longer the crisis, the more destructive is the impact on human suffering. The Kazakh government acted early to contain the spread of COVID-19. Following the announcement of a state of emergency, a state commission was set up to coordinate the efforts to fight the pandemic, impose quarantine control,and provide support to those whose livelihood was affected by the coronavirus or by the emergency restrictions. The authorities implemented a fiscal package to provide support to firms and households affected by the crisis. This effective approach to control the pandemic and improve access to health services should be continued and strengthened. But deployment of resources and reforms are also needed for Kazakhstan to navigate out of the crisis. The authorities may want toredeploy some resources from state programs toward improving access to and quality of education and healthcare, and for temporarily supporting workers and employers. Having a medium-termreform program can also help leverage resources from the private sector and better enable it to adjust and respond to new opportunities. The Kazakhstan Economic Update (KEU) is a semiannual report analyzing recent economic developments, prospects, and policy issues in Kazakhstan. The report draws on available data reported by the government, the National Bank of Kazakhstan (NBK), and additional information collected as part of the World Bank Group’s regular economic monitoring.